2020
DOI: 10.1002/adhm.201901366
|View full text |Cite
|
Sign up to set email alerts
|

H‐Ras Transformation of Mammary Epithelial Cells Induces ERK‐Mediated Spreading on Low Stiffness Matrix

Abstract: Oncogenic transformation of mammary epithelial cells (MECs) is a critical step in epithelial‐to‐mesenchymal transition (EMT), but evidence also shows that MECs undergo EMT with increasing matrix stiffness; the interplay of genetic and environmental effects on EMT is not clear. To understand their combinatorial effects on EMT, premalignant MCF10A and isogenic Ras‐transformed MCF10AT are cultured on polyacrylamide gels ranging from normal mammary stiffness, ≈150 Pa, to tumor stiffness, ≈5700 Pa. Though cells spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the effects of stiff and soft stroma on different types of cancer cells are not always the same. In most cases, the stiff substrate could promote EMT while soft substrate inhibits, but some studies have shown that the soft substrates cultivation of cells undergoes the EMT process more apparently, [ 79 , 80 , 104 ] which suggests the complex effects of the ECM stiffness. Early studies mainly focused on breast, liver, and lung cancer and gradually involved other tumor fields in recent years, but the specific mechanism in diverse cancers has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of stiff and soft stroma on different types of cancer cells are not always the same. In most cases, the stiff substrate could promote EMT while soft substrate inhibits, but some studies have shown that the soft substrates cultivation of cells undergoes the EMT process more apparently, [ 79 , 80 , 104 ] which suggests the complex effects of the ECM stiffness. Early studies mainly focused on breast, liver, and lung cancer and gradually involved other tumor fields in recent years, but the specific mechanism in diverse cancers has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…This diffusion is driven by ERK activation rather than typical mechanosensitive pathways such as YAP and TGFβ or myosin contraction. [ 79 ] In addition, an increase in matrix stiffness leads to an increase in cytoskeletal tension, which downregulates SOX4, a transcription factor maintaining the mesenchymal phenotype of breast cancer cells, and downstream mesenchymal marker expression, while the expression of other EMT‐related transcription factors (EMT‐TFs) remains unaffected. TRPM7, a regulator involved in mechanical sensory processes, could reduce cytoskeletal tension to promote the expression of SOX4.…”
Section: Mechanotransduction Of Tme On Emtmentioning
confidence: 99%
“…The combination of our model and the cell line series highlighted the effectiveness of the cell lines to capture phenotypes associated with various stages of breast cancer. All MCF10 cell lines adhered to the lumen surface in both collagen conditions, which was interesting as these cells have also been recently observed to form spherical, acinar structures when seeded in the presence of 2% Matrigel on top of flat, soft (elastic modulus ~ 150 Pa) polyacrylamide gels60 . We performed morphological characterizations of the cells, from tissue-scale observations of cell organization to the cell morphology on the luminal surface, and compared them to the well-established MCF7 cell line that is also used for modeling DCIS.…”
mentioning
confidence: 85%
“…Because adhesion affects the cytoskeletal remodelling in adherent cells and vice versa, it is hard to dissect the direct cause of RAS-induced changes to the mechanical responses of cells in complex environments. One study looking at the impact of changes in substrate stiffness to the behaviour of KRAS-transformed cells [ 17 ] showed that cells spread on soft substrates (150 Pa) in an ERK-dependent manner, but not on stiffer substrates (5.7 kPa), closer to those found in fibrotic tumours [ 44 ]. In this case, the inhibition of myosin by the treatment of cells with blebbistatin did not impact cancer cell spreading, implying a role for myosin-independent regulators of cell spreading, such as cell–substrate adhesion, in this change in cell spreading behaviour.…”
Section: Ras Alters Cell–ecm Interactionsmentioning
confidence: 99%